Description of three new species of Glyphepomis Berg (Heteroptera: Pentatomidae: Pentatominae) - Bianchi, Filipe Michels; Gonçalves, Valdenar Da Rosa; Souza, Joseane Rodrigues De; Campos, Luiz Alexandre (Zootaxa, 2016)
Three new species of the Glyphepomis are described: Glyphepomis dubia Campos & Souza, sp. nov., Glyphepomis amazonica Gonçalves & Campos, sp. nov. and Glyphepomis magnocephala Bianchi & Campos, sp. nov. Comparative illustrations of external and internal genitalia, distribution map of the described species, additions to the genus description, and a key to the species are provided.